Detection of phytophthora cactorum in the irrigation water in commercial orchards of 'Bartlett' pear in Villa Regina, Rio Negro - Rivero, Victoria Ileana (2011)
Trabajo presentado al XI International Pear Symposium, Argentina, 2010